Upstander - Preller, James (Feiwel and Friends, 2021)
"Mary O'Malley is tired of keeping secrets. Secrets like her older brother, Jonny's, drug use...When two girls Mary thought were her friends decide to slam another girl online, Mary tries to look the other way. Then the girls turn on Mary, and suddenly, she doesn't have a safety zone. Her brother is out of control, her family's energies are all spent on him. There is only one person she can turn to"--